Moving beyond sodium valproate: choosing the right anti-epileptic drug in children. (13th August 2019) - Balagura, Ganna; Iapadre, Giulia; Verrotti, Alberto; Striano, Pasquale
ABSTRACT: Introduction : Sodium valproate is a widely used anti-epileptic drug with a broad spectrum of activity and mechanism of action. It has consequently been the first-line drug for most seizure types in children for the past fifty years. A wide range of side effects come along with these exceptional properties, including teratogenicity and neuro-cognitive impairments in offspring. Therefore, epilepsy treatment in children and adolescents should be reassessed in light of newer antiepileptic drugs as well as a more targeted-approach with older drugs. Areas covered : The authors review the main concerns of valproate use in terms of adverse effects on different systems and drug interactions. The current alternatives to valproate in absence, myoclonic, tonic-clonic and focal onset seizures in children/adolescents are also reviewed. Expert opinion : There are several issues that research should address in antiepileptic therapy and in clinical studies with children, given the peculiarity of this population. Future perspectives in epilepsy therapy should now lead towards an individualized treatment.